Pengaruh Radiasi Gelombang Elektromagnetik pada Ponsel terhadap Kesehatan Manusia - Muhammad Subhan Aditya; Apipah Apipah; Elpi Purnamasari; Muhammad Taufiq Hidayatullah Syari; Diyajeng Luluk Karlina (Pusat Riset dan Inovasi Nasional, 2024)
The development of communication technology, especially mobile phones, has brought significant changes to everyday life. Their widespread use has made cell phones not only a communication tool but also a multifunctional device that influences many aspects of life. Along with the widespread use of cell phones, concerns have also emerged about the impact of electromagnetic wave radiation caused by cell phones on the human body. This research aims to analyze the effect of cell phone electromagnetic radiation on health using a literature study method, namely by taking data from several journals which are then reviewed based on the research title. And the research results obtained suggest that the radiation emitted by cellphones can potentially cause health problems such as brain tumors, stress and headaches. To prevent the impact of this radiation, we as cellphone users must be more careful in their use by not using cellphones excessively and must pay attention to the visibility when looking at the screen when in use. Keywords: Health, Cell Phones, Electromagnetic Radiation.